Tasawuf dalam Perspektif Psikologi: Harmoni Spiritual dan Kesehatan Mental - Ema Fitriya; Nur Hani'ah; Hanifatul Khofifah (AJMIE: Alhikam Journal of Multidisciplinary Islamic Education, 2024)
This article explores the relationship between Sufism and modern psychology, particularly in supporting mental health and spiritual harmony. Sufism, as a branch of Islamic spirituality, offers a holistic approach through practices such as tazkiyatun nafs, muraqabah, and dhikr to achieve inner peace and balance. This approach aligns with modern psychological concepts, such as emotional regulation and mindfulness, which emphasize the importance of emotional balance and life meaning. Through a literature review method, this article finds that Sufi principles can be adapted into psychological therapy to address stress, anxiety, and inner conflicts. By bridging Islamic spirituality and psychology, this article opens opportunities for deeper integration in creating holistic and value-based therapeutic approaches. This is particularly relevant in addressing the increasingly complex mental health challenges of the modern era